Enchanted - Malvey, Victoria (New York, U.S.A., Sonnet Books, 1999)
Lord Crispin Merrick and Amelia Ralston were childhood playmates -innocents frolicking on the grounds of hunterdon estate.
1 London, England 2 Dovedale, England
Keywords: ENGLISH LITERATURE; ROMANTIC LITERATURE; ROMANTIC STORY